BRAND AMBASSADOR, MINAT BELI PADA SHOPEE - Subagiyo Subagiyo; Arief Rahman; Ani Aprilliani (POLITEKNIK LP3I JAKARTA, 2023)
This study aimed to determine the brand ambassador at Shopee, to determine consumer buying interest, and to find out how much the influence of the Brand Ambassador on Buying Interest at Shopee in Ciodeng Village, Sindangresmi District, Pandeglang Regency. This study used descriptive quantitative research methods, used a sample of 100 respondents with probability sampling technique. Based on the results of research on brand ambassadors, out of a total of 100 respondents who were given 10 statements, it was concluded that the brand ambassadors used by Shopee are good. Furthermore, consumers’ buying interest at Shopee in Ciodeng Village, Sindangresmi District, Pandeglang Regency obtained a value of 2.94, the number was in the interval 2.52 – 3.27 with a high/good category. The results of the correlation analysis obtained an r value of 0.360, based on the correlation coefficient interval (0.200 – 0.399) which stated that there was a weak level of influence. While the coefficient of determination of 13% could be interpreted that the brand ambassador variable contributes 13%. Then the results of the correlation significance test using the hypothesis t test, it is known that tcount is greater than ttable, namely 3.825 > 1.671. This proved that H0 was rejected and Ha was accepted. So basically there was a positive and significant influence brand ambassadors on buying interest at Shopee in Ciodeng Village, Sindangresmi District, Pandeglang Regency.Keywords: Brand Ambassador, Buying Interest, Shopee.